2015
DOI: 10.21101/cejph.a4040
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cat Scratch Disease Cases Reported from Turkey between 1996 and 2013 and Review of the Literature

Abstract: This pooled analysis which enabled the evaluation of a large number of CSD cases, indicated that careful evaluation of clinical findings and histopathological investigation will provide valuable support for diagnosis and treatment of CSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Rifampicin 14 mg/kg/24 hours for 14 days as oral administration was preferred among the options as it was appropriate according to her age. 5 - 7 In the follow-up, it was observed that the patient’s tremor improved, and ataxia decreased significantly 1 month after the Rifampicin treatment, which was administered orally for 14 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rifampicin 14 mg/kg/24 hours for 14 days as oral administration was preferred among the options as it was appropriate according to her age. 5 - 7 In the follow-up, it was observed that the patient’s tremor improved, and ataxia decreased significantly 1 month after the Rifampicin treatment, which was administered orally for 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…The patient came into contact with the cat during the autumn-winter season when Bartonella henselae illness is more prevalent. 5 - 7 After 1 month of incubation, the patient developed submandibular lymphadenopathy, fever, and mastoiditis and was administered with amoxicillin-clavulanate. We learned that her neurological development was appropriate according to her age, and her neurological findings were noticed for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the patient history, reliability of laboratory tests and difficulties in performing biopsies, it seems highly unlikely that all these criteria can be simultaneously satisfied in a patient. Even if contact with a cat is common, skin lesions due to scratches or bites are detected in only 60% of documented CSD cases [ 7 ]. Moreover, poor attention is generally paid to the potential role of dogs in B. henselae infection transmission as these pets have been found implicated in approximately 5% of cases [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zoonoses are diseases that can be transmitted from animals to people. Cat-related zoonotic conditions can be associated with bacteria, dermatophytes, fleas, fungi, mites, mycobacteria, nematodes, protozoa, ticks, and viruses (Table 1 ) [ 1 - 10 ]; whether the cat is a mostly indoor or a mostly outdoor animal probably makes a difference in the likelihood of becoming a vector in the transmission of infectious organisms. Our patient presented with a distinctive cat-induced skin condition consisting of numerous punctures and small excoriations in a clustered appearance that, to the best of our knowledge, has not been previously named.…”
Section: Discussionmentioning
confidence: 99%